A Study on Pattern of Poisoning Cases in a Tertiary Care Hospital, Bangalore - S, Abubakar; K, Githa; N, Kiran; S, Sreebala (Indian Journal of Pharmacy Practice)
Poisoning is a common medico-social problem now days all over the world. It is estimated that up to half a million people die each year as a result of poisoning, due to pesticides and natural toxins. Objectives: To determine the socio demographic profile of the poisoning cases reported and to find out the pattern of poisoning cases at a tertiary hospital. Methodology: A Hospital based prospective study was conducted at KIMS hospital Bangalore. Patient data relevant to the study was recorded in a suitably designed patient proforma. The collected data was analysed using descriptive statistical analysis. Results: Majority (43.6%) of poisoning cases were found in the age group (21-30). Most of the patients were from urban region (66.5%). The population with possibility of exposure to poisoning in their occupations were farmers (31.5%), housewives (21.5%) and students (18.8%). In the study, the maximum numbers of poisoning cases reported were due to organophosphorus (33.3%) and drug overdose (20%). The number of intentional poisoning cases (73.63%) were more when compared to accidental poisoning cases (23.03%). 33% of poisoning cases showed a mean duration of hospitalization of 4-7 days Conclusion: This study clearly highlights that the maximum number of victims were in between 21- 30 years with slight male predominance. The most common manner of poisoning was suicidal with oral ingestion. Farmers have been found to be a major risk group by occupation.
Keywords: Pattern of poisoning; organophosphorous; Snake Bite; suicidal